Difference in differences analysis evaluates the effects of the badger control policy on bovine tuberculosis in England - Colin P. D. Birch; Mayur Bakrania; Alison Prosser; Dan Brown; Susan M. Withenshaw; Sara H. Downs (Scientific Reports)
Abstract Persistent tuberculosis (TB) in cattle populations in England has been associated with an exchange of infection with badgers (Meles meles). A badger control policy (BCP) commenced in 2013. Its aim was to decrease TB incidence in cattle by reducing the badger population available to provide a wildlife reservoir for bovine TB. Monitoring data from 52 BCP intervention areas 200–1600 km2 in size, starting over several years, were used to estimate the change in TB incidence rate in cattle herds, which was associated with time since the start of the BCP in each area. A difference in differences analysis addressed the non-random selection and starting sequence of the areas. The herd incidence rate of TB reduced by 56% (95% Confidence Interval 41–69%) up to the fourth year of BCP interventions, with the largest drops in the second and third years. There was insufficient evidence to judge whether the incidence rate reduced further beyond 4 years. These estimates are the most precise for the timing of declines in cattle TB associated with interventions primarily targeting badgers. They are within the range of previous estimates from England and Ireland. This analysis indicates the importance of reducing transmission from badgers to reduce the incidence of TB in cattle, noting that vaccination of badgers, fertility control and on farm biosecurity may also achieve this effect.